PSYCHOLINGUISTIC BASIS OF LISTENING COMPREHENSION (World Bulletin of Social Sciences, 2023)
The article examines the theoretical information on listening comprehension skills and explores the psycholinguistic foundations of listening comprehension skills. The effect of listening comprehension on the quality of education and the difficulties in this process, the experiences of practical teaching of listening and comprehension in various ways are covered as much as possible